The effects of post-thermal annealing on the optical parameters of indium-doped ZnO thin films - 彭丽萍 方亮 吴卫东 王雪敏 李丽 (Chinese physics B, 2012)
Indium-doped ZnO thin films are deposited on quartz glass slides by RF magnetron sputtering at ambient temperature. The as-deposited films are annealed at different temperatures from 400℃ to 800 ℃ in air for 1 h. Transmittance spectra are used to determine the optical parameters and the thicknesses of the films before and after annealing using a nonlinear programming method, and the effects of the annealing temperatures on the optical parameters and the thickness are investigated. The optical band gap is determined from the absorption coefficient. The calculated results show that the film thickness and optical parameters both increase first and then decrease with increasing annealing temperature from 400℃ to 800℃. The band gap of the as-deposited ZnO：In thin film is 3.28 eV, and it decreases to 3.17 eV after annealing at 400℃. Then the band gap increases from 3.17 eV to 3.23 eV with increasing annealing temperature from 400℃ to 800℃.